Students’ Perception of the Use Podcast in Speaking Ability in Learning Speaking - Syafira Tri Ananda; Syafryadin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
This research aimed to find out students’ perception of the use podcast in speaking ability in learning speaking and to know positive or negative response students’ of using podcast. The reserachers used a quantitative research design as a methodogy. The instrument for collecting data in this study is questionnaire, adapted from the work of Bawanti & Arifani (2021).The sample of this research is fourty three students from class A these students are specifically from the pool of first-semester students at the Faculty of Animal Husbandry at Bengkulu University during the academic year 2023–2024 It uses a Likert Scale with four distinct categories: